Between Global Economic Shocks and Institutional Capacity: Explaining Fiscal Resilience in Timor-Leste - Egídio Maria de Jesus Gomes; Frasto Biyanto; Miswanto; Baldric Siregar; Ananias Barreto; Helio Augusto da C. Xavier Mauquei; Apolinario Magno (LP2M IAIN Palopo, 2026)
Timor-Leste faces significant fiscal challenges arising from its heavy dependence on petroleum revenues, exposure to global economic shocks, and the need to strengthen institutional capacity in the post-conflict development period. This study examines the effects of global economic dynamics and institutional capacity on fiscal resilience in Timor-Leste. A quantitative cross-sectional research design was employed using a structured Likert-scale questionnaire administered to 200 academics selected through stratified random sampling from accredited universities in Timor-Leste. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The measurement model demonstrated satisfactory reliability and validity, while the structural model exhibited strong explanatory power (R² = 0.705). The findings reveal that global economic dynamics have a significant negative effect on fiscal resilience (β = −0.715, p < 0.001), whereas institutional capacity has a significant positive effect on fiscal resilience (β = 0.459, p < 0.001). Together, both variables explain approximately 70.5% of the variance in fiscal resilience, indicating that external economic conditions and institutional quality are key determinants of fiscal sustainability in Timor-Leste. These findings highlight the importance of reducing dependence on petroleum revenues while strengthening public financial management, governance quality, and institutional effectiveness to enhance fiscal resilience. The study contributes to the literature on fiscal resilience in resource-dependent small states and provides evidence to support policy reforms aimed at improving long-term fiscal sustainability.